Spatial relationships between the standing vegetation and the soil seed bank in a fire-prone encroached dehesa in Central Spain - Torres, Ivan; Cespedes, Blanca; Perez, Beatriz; Moreno, Jose M (PLANT ECOLOGY, 2013)
Postfire vegetation regeneration in many fire-prone ecosystems is soil seed bank dependent. Although vegetation and seed bank may be spatially structured, the role of prefire vegetation patterns and fire in determining postfire vegetation patterns is poorly known. Here, we investigated the spatial patterning of species abundance and richness in the vegetation and seed bank of a Mediterranean encroached dehesa in Central Spain. The seed bank was studied with and without a heat shock simulating a spatially homogeneous fire. Semivariograms and cross-semivariograms showed that species richness in the vegetation was aggregated in patches, mainly of herbs, with highest values corresponding to high herb cover and low tree cover. Species richness in the seed bank was also structured in patches, but the spatial pattern was weak. Seedling density of germinates in the seed bank also showed weak spatial pattern. Heating increased overall germination and species richness, and the intensity of the spatial pattern of species richness, particularly of herbaceous species. However, seed bank density patterns disappeared after heat shock because of increased germination of shrubs without spatial pattern. Our results document that the spatial structure of plant richness in the vegetation may persist after fire due to the spatial patterns of herbaceous species in the seed bank, and that postfire species richness patterns can arise independently of fire intensity patterns. However, the spatial structure of the vegetation after fire can be altered by the feedback between shrub encroachment and an eventual fire because of the ubiquitous germination of shrubs.
Keywords: Land abandonment; Land-use change; Seeder; Semivariogram; Species richness

Vegetation and soil seed bank relationships across microhabitats in an abandoned Quercus suber parkland under simulated fire - Torres, Ivan; Urbieta, Itziar R; Moreno, Jose M (Ecoscience, 2012)
Mediterranean agro-forestry systems are undergoing rapid change due to abandonment. This turns formerly cultivated or grazed oak-tree parklands (i.e., savanna-type formations called “dehesas”) into flammable formations of scattered trees within a matrix of shrubs with open spaces. Wildfires can now occur, threatening the persistence of these formations. Fire-prone shrublands commonly regenerate after fire from seeds stored in the soil. Understanding the relationships between standing vegetation and the soil seed bank across microhabitats can help predict the response of the system in case of fire. Here we investigated these relationships in an abandoned Quercus suber (cork oak) dehesa in central Spain. Vegetation and soil were sampled and assigned to different microhabitats: under the trees (TRC), in dense shrub cover (DSC), and in low shrub cover (LSC). A heat shock was applied to half of each sample to simulate fire; the other half served as control. Both sets of samples were then germinated in a greenhouse. Almost 90% of the species were herbs, while the rest were woody shrubs. The number of species recorded in TRC and DSC was lower than in LSC, in which species richness, particularly herbs, was maximal. Heating increased the total number of species that germinated, but mean species richness per sample was not altered. Heating markedly increased the number of germinations in all microhabitats, particularly those of woody species. Furthermore, the germination of shrubby species increased in the 3 microhabitats, notably in TRC. While the standing plant community was well differentiated among microhabitats, this was not the case for the soil seed bank, which was homogeneous across microhabitats, with or without heating. We conclude that the high density of shrubby seeds found in TRC or in the other microhabitats presents substantial threats to the persistence of Q. suber parklands in case of fire.
Keywords: cistus; Cork oak; Dehesa; Encroachment; Erica; Mediterranean shrublands